Study of effective laying pattern of permeable interlocking concrete paver for storm-water management - Chow M.F.; Ng J.W.; Chong S.T. (Institute of Physics Publishing, 2023)
Green computing; Runoff; Skid resistance; Storms; Stretchers; Water management; Coverage area; Infiltration rate; Laying patterns; Permeable interlocking concrete pavers; Ring method; Storm-water managements; Stretcher bonds; Wet conditions; Infiltration